2019
DOI: 10.1016/j.heliyon.2019.e02274
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation following sub-lethal oral exposure of cypermethrin in rats: mitigating potential of epicatechin

Abstract: Cypermethrin (CYP), a synthetic pyrethroid is a common environmental toxicant owing to its wide usage as a broad-spectrum insecticide. Its exposure to non-target organisms, including man, elicits numerous adverse effects making it a major public health issue. Epicatechin (EC) has proven anti-oxidative and anti-inflammatory properties. The present study was undertaken to evaluate the protective efficacy of epicatechin with regards to altered oxidative and inflammatory parameters subsequent to CYP treatment in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 83 publications
4
30
0
Order By: Relevance
“…When they get saturated GPX is activated that to detoxifies H 2 O 2 . Similar to other studies, oxidative stress is increased with a decreased level of GPX, SOD & CAT activities in group II [21,23] . In PBMC + withdrawal group (Group III) partial recovery of these enzymes was evident in our study.…”
Section: Discussionsupporting
confidence: 90%
“…When they get saturated GPX is activated that to detoxifies H 2 O 2 . Similar to other studies, oxidative stress is increased with a decreased level of GPX, SOD & CAT activities in group II [21,23] . In PBMC + withdrawal group (Group III) partial recovery of these enzymes was evident in our study.…”
Section: Discussionsupporting
confidence: 90%
“…There are many reports confirming that exposure on pyrethroids causes oxidative stress and in this mechanism causes an increase in the expression of genes encoding proinflammatory cytokines [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The interleukin1β is primarily synthesized in macrophages and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A known and major cause for such cell killing is oxidative stress which, above a threshold, is very damaging, even fatal, to any human/non-human cell 40 , 41 . Several studies have reported that pyrethroids can induce oxidative stress condition leading to cell damage and death 42 44 . Well known markers of oxidative stress include monitoring lipid and protein oxidation and levels of glutathione (reduced and oxidised).…”
Section: Discussionmentioning
confidence: 99%